Neonatal admission from emergency department (Journal of Patan Academy of Health Sciences, 2020)
Neonatal period is a vulnerable period of life. In Nepal, most common causes of newborn admission in the neonatal intensive care unit (NICU) are birth asphyxia, neonatal sepsis. This study explores the diseases with which 131 neonates were admitted from emergency department. Sepsis was the main cause of admission, followed by pneumonia.